Kinetics of peripheral blood stem cell mobilization following G-CSF-supported chemotherapy - Seggewiß-Bernhardt, Ruth; Buß, Eike Christian; Herrmann, Doris; Goldschmidt, Hartmut; Ho, Anthony Dick; Frühauf, Stefan (Stem cells, 2003)
It would be a clinical and economical advantage if the optimal time point of peripheral blood stem cell (PBSC) mobilization following G-CSF-supported chemotherapy (CT) was known in advance. Therefore, we retrospectively analyzed mobilization parameters in 113 adult tumor patients treated in our institution within 1 year. The start of apheresis was guided by CD34+ cell measurements in the PB and occurred on or after day 11 after start of mobilization CT in 97% of patients. The median peak (p)CD34+ cell count in PB uniformly occurred on day 14-15 (range: 6-32 days) after the start of CT, irrespective of the diagnosis (multiple myeloma n = 76, other histology n = 37), the type, but not the amount, of premobilization CT or radiotherapy (RT), the mobilization regimen, or the G-CSF dosage administered. Among more heavily pretreated patients (>six cycles of prior CT or RT), a higher proportion mobilized late (pCD34+ cell count later than day 20 in 12% and 13%, respectively, versus 2%-5% in the other groups). Therefore, we propose to start measuring CD34+ cells in the PB on day 11 after the start of mobilization therapy. The wide range of optimal mobilization time points argues for an individualized rather than a preset start of apheresis.
Elektronische Reproduktion der Druckausgabe
Gesehen am 10.12.2021